Relevance of Hindi Sociolinguistics in the Digital Age: डिजिटल युग में हिंदी समाजभाषाविज्ञान की प्रासंगिकता - Madhale, Shahu Dasharath (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This research paper analyzes the changing role and relevance of Hindi sociolinguistics in the digital era. The rapid expansion of digital media has brought fundamental changes to the use, spread, and structure of the Hindi language. To understand these transformations, the theoretical framework of sociolinguistics provides an essential foundation. The central argument of this study is that the digital environment has redefined Hindi as a dynamic, multidimensional, and continuously evolving socio-cultural entity, making the role of sociolinguistics crucial in decoding this new linguistic reality. The paper examines key features of digital Hindi—such as linguistic hybridity, the emergence of new registers, the democratization of language through social media, and the role of language in constructing online identity—from a sociolinguistic perspective. Ultimately, the study concludes that in the digital age, Hindi sociolinguistics is no longer confined to academia; it has become a vital practical tool for shaping language policy, education, technology, and cultural studies. Abstract in Hindi Language: डिजिटल युग में हिंदी समाजभाषाविज्ञान की बदलती हुई भूमिका एवं प्रासंगिकता का विश्लेषण यह शोधपत्र प्रस्तुत करता है। डिजिटल माध्यमों के प्रसार ने हिंदी भाषा के प्रयोग, प्रसार और स्वरूप में जो मौलिक परिवर्तन किए हैं, उन्हें समझने के लिए समाज भाषा विज्ञान के सिद्धांत एक अनिवार्य ढाँचा प्रदान करते हैं। शोधपत्र का केंद्रीय तर्क यह है कि डिजिटल वातावरण ने हिंदी भाषा को एक गतिशील, बहु-आयामी और निरंतर विकसित होने वाली सामाजिक-सांस्कृतिक इकाई के रूप में पुनर्परिभाषित किया है, और इस नई भाषाई वास्तविकता को डिकोड करने में समाज भाषा विज्ञान की भूमिका अत्यंत महत्वपूर्ण हो गई है। यह शोध डिजिटल हिंदी की प्रमुख विशेषताओं—जैसे भाषाई संकरता, नए विविध रजिस्टरों का उदय, सोशल मीडिया द्वारा भाषा का लोकतंत्रीकरण, और ऑनलाइन पहचान निर्माण में भाषा की भूमिका—का समाज भाषावैज्ञानिक दृष्टि से विश्लेषण करता है। अंततः, यह पत्र इस निष्कर्ष पर पहुँचता है कि डिजिटल युग में हिंदी समाज भाषा विज्ञान केवल एक शैक्षणिक अनुशासन न रहकर, भाषा नीति, शिक्षा, प्रौद्योगिकी और सांस्कृतिक अध्ययनों के लिए एक महत्वपूर्ण व्यावहारिक उपकरण बन गया है। Keywords: समाज भाषा विज्ञान, हिंदी, डिजिटल संचार, भाषाई परिवर्तन, सोशल मीडिया, कोड-मिक्सिंग, भाषा नीति, ऑनलाइन पहचान।